Building Stability On Permafrost In Vorkuta, Russia - Pavel I. Kotov; Vanda Z. Khilimonyuk (Geography, Environment, Sustainability, 2021)
The Infrastructure stability on permafrost is currently an important topic as the Arctic countries are developing climate change adaptation and mitigation programs. Assessing the sustainability of infrastructure facilities (especially in urban environments) is a difficult task as it depends on many parameters. This article discusses the city of Vorkuta, which is located in the northwest of Russia. This city differs from many others built on permafrost because most of buildings were built according to Principle II (The Active Method) of construction on permafrost with thawing soil prior to construction. Assessments of the engineering and geocryological conditions, basic principles of construction in the city, and reasons for building failures, were carried out within this study. The research is based on publications, open data about buildings, and visual observations in Vorkuta. About 800 buildings are in use in Vorkuta in 2020 (43% of what it was 50 years ago). According to the analysis, about 800 houses have been demolished or disconnected from utility lines over the past 50 years (about 250 of these are still standing, pending demolition). Since 1994, the construction of new residential buildings has almost stopped. Therefore, buildings that have been in use for over 50 years will account for 90% of the total residential housing stock by 2040. The effects of climate change in the city will depend primarily on the principle of construction employed and on the geocryological conditions of the district. Buildings constructed according to Principle I (The Passive Method) were found to be more vulnerable due to a decrease in permafrost bearing capacity. The impact of increasing air temperature on some of the buildings built on bedrock (the central part of the city) and some built on thawing soil will be minimal, as other factors are more significant.